Self-Monitoring of Blood Pressure in Hypertension: A UK Primary Care Survey - S. Baral-Grant; M. S. Haque; A. Nouwen; S. M. Greenfield; R. J. McManus (International Journal of Hypertension)
This study aimed to determine the prevalence of Self-Monitoring Blood Pressure amongst people with hypertension using a cross-sectional survey. Of the 955 who replied (53%), 293 (31%) reported that they self-monitored blood pressure. Nearly 60% (198/331) self-monitored at least monthly. Diabetic patients monitoring their blood glucose were five times more likely than those not monitoring to monitor their blood pressure. Self-monitoring is less common in the UK than internationally, but is practiced by enough people to warrant greater integration into clinical practice.